BALANITES KERNEL OIL FOR THE TREATMENT OF DERMATOPHYTES: A CLINICAL TRIAL - Mohamed Toum, Abdalla; Osman, Nour Ahmed; Abdelrahman, Elnour Elamin; Hussein, Ismail Hassan; Ahmed Elhussein, Salah (Gezira Journal of Health Sciences, 2006)
In a previous in vitro study, we have shown that the kernel oil of fruits of the tree Balanites aegyptiaca referred to as Balanites kernel oil ((BKO) is active against dermatophytes (i.e. superficial mycosis, ringworms, tineas (T. captitis, T. cercinata and T. pedis). We report here our clinical trials with BKO. Trials were performed on patients presenting at Wad Medani Dermatology Teaching Hospital as well as primary school children in Elsoreeba Town (5 km south of Wad Medani). Not all patients followed treatment till completely cured. Patients treated with BKO (half of the total) achieved complete cure in 3-5 weeks, on average, while those treated with the standard antifungal drug Miconazole (half of the total patients) did the same in the longer period of 3-8 weeks. Photographs showing progress of response to BKO treatments are included. BKO has great potential for development as a commercial drug for the treatment of dermatophytes.